Flexible functional ceramic-based composite film and preparation method thereof

By blending ceramic materials with nanoaramid fiber solution, and using scraping technology and protic solvent curing method, a flexible functional ceramic matrix composite film with a heterogeneous structure is prepared, solving the problem of the decline in functionality of traditional materials when improving flexibility, and achieving high flexibility and high functionality of ceramic materials.

CN119707356APending Publication Date: 2025-03-28TSINGHUA SHENZHEN INTERNATIONAL GRADUATE SCHOOL
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510027318.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

While improving flexibility, traditional flexible functional ceramic matrix composite materials have reduced functionality such as thermal conductivity, making it difficult to take into account both flexibility and functionality.

Method used

By mixing the dimethyl sulfoxide solution containing ceramic material with the nanoaramid fiber solution, a coating liquid film is formed by scraping technology, and curing it in a protic solvent to remove impurities to obtain a flexible functional ceramic matrix composite film with a heterogeneous structure.

Benefits of technology

It has achieved high filling amount of ceramic materials and low nano-aramid fiber usage, improved the flexibility and functionality of ceramic materials, and is suitable for the preparation of a variety of ceramic materials, with wide applicability and industrial production potential.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119707356A_ABST
    Figure CN119707356A_ABST
Patent Text Reader

Abstract

The invention discloses a flexible functional ceramic-based composite film and a preparation method thereof, and the preparation method comprises the following steps: mixing a dimethyl sulfoxide solution containing a ceramic material with a nano aramid fiber solution to obtain a precursor solution; blade-coating the precursor solution on the surface of a carrier to form a coating liquid film; and after the coating liquid film is soaked in a protic solvent for curing, the protic solvent is removed, and the flexible functional ceramic-based composite film is obtained. According to the preparation method provided by the invention, the usage amount of a macromolecular binder aramid fiber can be reduced while the filling amount of the ceramic is increased, and the comprehensive improvement of the functionality and the flexibility of the flexible functional ceramic-based composite film is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of composite materials, and in particular to a flexible functional ceramic-based composite film and a preparation method thereof. Background Art

[0002] The ionic bonds in ceramic materials are highly directional, and it is difficult for them to undergo plastic deformation to release energy when subjected to external forces. They can only release energy through the formation and expansion of cracks. This brittle fracture behavior limits the flexibility of ceramic materials, resulting in their inability to meet performance requirements in certain application scenarios. Therefore, the development of ceramic-based composites with higher flexibility has become a key research direction in the field of materials science, and flexible functional ceramic-based composite films are one of the most widely used types of ceramic-based composites.

[0003] However, the traditional preparation method of flexible functional ceramic-based composite materials usually requires the addition of a large amount of polymer binders. Although these polymer materials can enhance flexibility, they will also lead to a decrease in the functionality of the ceramic materials, such as a decrease in thermal conductivity, making it difficult to achieve the compatibility of flexibility and excellent functionality. Summary of the invention

[0004] In view of this, the present application provides a method for preparing a flexible functional ceramic-based composite film, which can efficiently prepare a flexible functional ceramic-based composite film with good flexibility and high ceramic functionality.

[0005] In addition, the present application also provides a flexible functional ceramic-based composite film prepared by the above-mentioned method for preparing the flexible functional ceramic-based composite film.

[0006] The present invention provides a method for preparing a flexible functional ceramic-based composite film, comprising the following steps: mixing a dimethyl sulfoxide solution containing a ceramic material with a nano-aramid fiber solution to obtain a precursor solution; Applying the precursor solution to the surface of the carrier by blade coating to form a coating liquid film; and After the coating liquid film is immersed in a proton solvent for solidification, the proton solvent is removed to obtain the flexible functional ceramic-based composite film.

[0007] In some possible embodiments, the preparation of the dimethyl sulfoxide solution containing the ceramic material comprises the following steps: mixing the ceramic material with the isopropyl alcohol solvent and grinding the mixture to obtain a ceramic material solution; and The isopropyl alcohol solvent in the ceramic material solution is replaced with a dimethyl sulfoxide solvent to obtain the dimethyl sulfoxide solution containing the ceramic material.

[0008] In some possible embodiments, in the step of grinding the ceramic material with the isopropanol solvent, the grinding speed is 300 rpm to 600 rpm, the grinding time is 24 h to 48 h, and the grinding includes ball milling and / or sand milling; and / or In the step of replacing the isopropanol solvent in the ceramic material solution with a dimethyl sulfoxide solvent, a centrifugal replacement method is adopted, and the conditions of the centrifugal replacement include: a rotation speed of 10000rpm~11000rpm, a time of 20min~25min, and a centrifugal number of 1~2 times.

[0009] In some possible embodiments, the ceramic material includes at least one of a zero-dimensional ceramic material, a one-dimensional ceramic material, and a two-dimensional ceramic material.

[0010] In some possible embodiments, the nano-aramid fiber solution is prepared by an alkaline lysis method, comprising the following steps: The aramid precursor is dissolved in a mixed solution of dimethyl sulfoxide and potassium hydroxide, and the mixture is heated and stirred to obtain the nano-aramid fiber solution.

[0011] In some possible embodiments, the nano-aramid fibers in the nano-aramid fiber solution include at least one of para-aramid, heterocyclic aramid, and meta-aramid.

[0012] In some possible embodiments, in the precursor solution, the mass ratio of the ceramic material to the nano-aramid fiber is (1-32):1.

[0013] In some possible embodiments, the linear speed of the coating is 20 mm / s to 90 mm / s; and / or The coating liquid film has a thickness of 250 μm to 1000 μm.

[0014] In some possible embodiments, the protic solvent includes at least one of water, alcohol and acid.

[0015] In addition, an embodiment of the present application further provides a flexible functional ceramic-based composite film, which is prepared by the above-mentioned method for preparing the flexible functional ceramic-based composite film.

[0016] Compared with the prior art, the method for preparing a flexible functional ceramic-based composite film provided in the embodiment of the present application uses a scraping technique to blend a dimethyl sulfoxide solution containing a ceramic material with a nano-aramid fiber solution, and combines the phase separation properties of the nano-aramid fiber to prepare a flexible functional ceramic-based composite film with a heterogeneous structure. This preparation method can increase the filling amount of ceramics and reduce the amount of aramid fiber (polymer binder) used. At the same time, a layer of nano-aramid fiber layer is formed on the surface of the ceramic material. Due to the uneven distribution of the nano-aramid fiber, when the flexible functional ceramic-based composite film is bent, the nano-aramid fiber layer can effectively disperse the stress on the ceramic material, avoid stress concentration, and improve the flexibility of the film, thereby achieving a comprehensive improvement in the functionality and flexibility of the flexible functional ceramic-based composite film.

[0017] In addition, this preparation method is suitable for the preparation of flexible functional ceramic-based composite films of a variety of ceramic materials and has wide applicability; and the use of scraping technology breaks through the limitations on film size and batch size, which is conducive to large-scale batch production of flexible functional ceramic-based composite films. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 A process flow chart of a method for preparing a flexible functional ceramic-based composite film provided in one embodiment of the present application. DETAILED DESCRIPTION

[0019] The following will clearly and completely describe the technical solutions in the embodiments of the present application in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments.

[0020] See also Figure 1 As shown, the method for preparing the flexible functional ceramic-based composite film provided in the embodiment of the present application specifically comprises the following steps: Step S1, mixing a dimethyl sulfoxide solution containing a ceramic material with a nano-aramid fiber solution to obtain a precursor solution.

[0021] Specifically, a dimethyl sulfoxide solution containing ceramic materials, i.e., a dimethyl sulfoxide-ceramic solution, is fully mixed with a nano-aramid fiber solution to form a uniform precursor solution. Dimethyl sulfoxide is a polar solvent with a strong dissolving ability, which is conducive to better dissolving ceramic materials and improving the mixing uniformity of ceramic materials and nano-aramid fibers. The polarity of dimethyl sulfoxide also helps to reduce the risk of agglomeration and coagulation of nano-aramid fibers. This step can meet the requirements of fully mixing ceramics and nano-aramid fibers under high ceramic addition and low nano-aramid fiber addition to obtain a uniform precursor solution.

[0022] The mixing method can be stirring, ultrasonic treatment, mechanical mixing or vibration mixing. It can be understood that the mixing method includes but is not limited to the above methods, and any method that can achieve good mixing of the dimethyl sulfoxide-ceramic solution and the nano-aramid fiber solution is acceptable.

[0023] In some embodiments, in the precursor solution, the mass ratio of ceramic material to nano-aramid fiber can be (1~32):1. Different mass ratios will affect the content of each component in the final prepared flexible functional ceramic-based composite film. Within the limited range of the above mixing ratio, the content of ceramic in the film can be increased while improving the flexibility of the film, thereby making the film have both excellent flexibility and good ceramic functionality. The preparation method of the present application is particularly useful for preparing flexible functional ceramic-based composite films with high ceramic content. The mass ratio of ceramic to nano-aramid fiber can be illustratively 1:1, 5:1, 15:1, 20:1, 25:1, 30:1, 32:1 or any value within the range formed by any two of the above values. The mass ratio of ceramic to nano-aramid fiber can further be (5~32):1.

[0024] In some embodiments, the mixing method may be stirring, and the stirring speed may be 100 rpm to 500 rpm, which is beneficial to improving the uniformity and stability of the precursor solution.

[0025] In some embodiments, the preparation of the dimethyl sulfoxide-ceramic solution may include the following steps: Step S11, mixing the ceramic material and the isopropyl alcohol solvent and grinding them to obtain a ceramic material solution.

[0026] Step S12, replacing the isopropyl alcohol solvent in the ceramic material solution with a dimethyl sulfoxide solvent to obtain a dimethyl sulfoxide-ceramic solution.

[0027] Among them, isopropyl alcohol is a non-polar material with low viscosity and good wettability, which helps to reduce the agglomeration between ceramic materials and promote the uniform dispersion of ceramic materials. More importantly, by grinding isopropyl alcohol and ceramic materials, isopropyl alcohol can be fully contacted with the ceramic materials, and the alcohol hydroxyl groups can be grafted onto the surface of the ceramic materials, thereby forming hydroxylated ceramic materials. The hydroxyl groups on the surface of the hydroxylated ceramic materials can interact with the nano-aramid fibers to form hydrogen bonds, thereby enhancing the interfacial bonding force of the flexible functional ceramic-based composite film.

[0028] In the nano-aramid fiber solution, the dispersed and stripped nano-aramid fibers are in a deprotonated state, and the amide groups (-CONH) of the nano-aramid fibers lose protons (H + ) into a negatively charged amide group (-CON -). The presence of this negative charge effectively reduces the interaction force between the nano-aramid fibers, allowing the nano-aramid fibers to be peeled off and stably dispersed in the solution. However, isopropyl alcohol is a weak proton solvent. Directly blending the ceramic solution with isopropyl alcohol as a solvent with the nano-aramid fiber solution will cause the nano-aramid fibers that have lost protons to be protonated again, which in turn triggers the proton regaining of the amide groups of the nano-aramid fibers and the reformation of hydrogen bonds between the nano-aramid fibers, resulting in the agglomeration of the nano-aramid fibers. This uneven agglomeration not only reduces the dispersibility of the material, but also affects the stability of the preparation process. In order to reduce this uneven agglomeration of the nano-aramid fibers, the isopropyl alcohol solvent is replaced with a dimethyl sulfoxide solvent, which can not only retain the hydroxyl groups on the surface of the ceramic particles, but also effectively prevent the undesirable agglomeration of the nano-aramid fibers, ensuring the uniform dispersibility of the material and the stability of the process.

[0029] As mentioned above, dimethyl sulfoxide is a polar solvent, which helps to maintain the deprotonated state of the nano-aramid fibers without causing the nano-aramid fibers to reacquire protons, further reducing the risk of agglomeration and coagulation of the nano-aramid fibers.

[0030] Using isopropyl alcohol to first disperse the ceramic material and then replacing the solvent with dimethyl sulfoxide is beneficial to further improve the performance and quality of the finally prepared flexible functional ceramic-based composite film.

[0031] In some embodiments, the grinding speed may be 300 rpm to 600 rpm, the grinding time may be 24 h to 48 h, and the grinding may include ball milling and / or sand milling. The above grinding conditions are conducive to uniform dispersion of the ceramic material and grafting the hydroxyl group of isopropanol to the surface of the ceramic material.

[0032] In some embodiments, the replacement can be carried out by centrifugal replacement. The conditions of the centrifugal replacement may include: a rotation speed of 10000 rpm to 11000 rpm, a time of 20 min to 25 min, and a centrifugation number of 1 to 2 times, which is conducive to removing isopropanol and effectively replacing the isopropanol solvent with a dimethyl sulfoxide solvent.

[0033] The ceramic material contained in the dimethyl sulfoxide-ceramic solution may include at least one of zero-dimensional ceramic material, one-dimensional ceramic material and two-dimensional ceramic material, etc., which has a wide range of applicability, is conducive to expanding the application field and market prospects of ceramic materials, and promoting their wide application in cutting-edge science and technology. Among them, zero-dimensional ceramic materials refer to nanoparticles or nanoparticles, which usually have uniformity in three-dimensional space and are at the nanometer level in size; one-dimensional ceramic materials refer to nanomaterials such as linear, filamentary or fibrous materials, which usually have a long length and a nanometer-level diameter; two-dimensional ceramic materials refer to thin film or sheet materials, which usually have a large area and a nanometer thickness.

[0034] In some embodiments, the material of the zero-dimensional ceramic material may include at least one of aluminosilicate, barium titanate, indium oxide, lead zirconate titanate, copper oxide, nickel oxide, zirconium oxide, titanium dioxide, aluminum oxide, cobalt oxide, iron oxide, lithium lanthanum zirconium titanium oxide, zirconium carbide, titanium carbide and molybdenum carbide.

[0035] In some embodiments, the material of the one-dimensional ceramic material may include at least one of alumina, zirconia, mullite, titanium dioxide, potassium titanate, silicon carbide, silicon nitride, boron nitride nanotubes, and the like.

[0036] In some embodiments, the material of the two-dimensional ceramic material may include at least one of titanium dioxide, titanium diboride, molybdenum disulfide, boron nitride nanosheets, zirconium nitride, aluminum nitride, and silicon nitride.

[0037] In some embodiments, the nano-aramid fiber solution can be prepared by alkaline lysis method, which can specifically include the following steps: The aramid precursor is dissolved in a mixed solution of dimethyl sulfoxide and potassium hydroxide, and heated and stirred to obtain the nano-aramid fiber solution. That is, the aramid precursor undergoes a cracking reaction in the mixed solution of dimethyl sulfoxide and potassium hydroxide after being heated and stirred, thereby obtaining nano-aramid fibers.

[0038] In some embodiments, the aramid precursor may include poly(p-aniline terephthalamide) fibers.

[0039] In some embodiments, the heating temperature may be 50° C. to 100° C., which is beneficial to accelerate the dissolution and chain breaking reaction of the aramid precursor and improve the yield and dispersibility of the nano-aramid fiber.

[0040] In some embodiments, the stirring speed may be 100 rpm to 500 rpm, which is conducive to uniform mixing of the aramid precursor with the mixed solution of dimethyl sulfoxide and potassium hydroxide, promoting contact between the reactants and increasing the reaction rate.

[0041] In some embodiments, the heating and stirring time can be 24 hours to 48 hours, which is conducive to the full progress of the cracking reaction and the full exfoliation and cracking of the aramid precursor.

[0042] In some embodiments, the nano-aramid fiber in the nano-aramid fiber solution may include at least one of para-aramid, heterocyclic aramid, and meta-aramid, which is conducive to meeting diversified application requirements. In addition, compared with micron-level fibers, nano-level aramid fibers have a larger specific surface area and excellent mechanical properties, which is conducive to enhancing the strength, toughness and thermal stability of the flexible functional ceramic-based composite film.

[0043] Step S2, coating the precursor solution on the surface of the carrier by scraping to obtain a coating liquid film.

[0044] Specifically, the scraping technology is used to apply the precursor solution once to the surface of the scraping substrate, and the precursor solution is preliminarily self-assembled to form a uniform coating liquid film, which simplifies the preparation process and improves production efficiency. This method makes the coating process easy to control, helps to optimize the thickness, uniformity and performance of the liquid film, and meets the requirements of industrial production. At the same time, the scraping technology has the characteristics of high efficiency and low consumables, reduces production costs and improves economy. In addition, scraping can achieve large-scale and mass production of flexible functional ceramic-based composite films, meeting the market's growing demand for flexible functional ceramic-based composite films. In addition, scraping can achieve a high ceramic addition amount, and the ceramic material is fully dispersed and combined in the coating liquid film through uniform scraping technology, further increasing the filling amount of ceramic materials in the flexible functional ceramic-based composite film.

[0045] Therefore, the implementation of scraping technology makes the preparation method of flexible functional ceramic-based composite films more in line with industrial production standards, providing solid technical support for efficient, stable and repeatable production processes.

[0046] In some embodiments, the line speed of the scraping coating can be 20 mm / s to 90 mm / s, which is conducive to balancing the coating uniformity and efficiency, improving the production stability, and further improving the performance and quality of the final flexible functional ceramic-based composite film. The line speed of the scraping coating can be 20 mm / s, 30 mm / s, 40 mm / s, 50 mm / s, 60 mm / s, 70 mm / s, 80 mm / s, 90 mm / s or any value within the range of any two of the above values. The line speed of the scraping coating can further be 40 mm / s to 70 mm / s.

[0047] In some embodiments, the thickness of the coating liquid film can be 250 μm to 1000 μm. The thickness of the coating liquid film affects the thickness of the obtained flexible ceramic-based composite film. Controlling the thickness of the coating liquid film is conducive to optimizing the mechanical properties and functionality of the flexible ceramic-based composite film to meet its needs in different application scenarios. The thickness of the coating liquid film can be 250 μm, 300 μm, 400 μm, 500 μm, 600 μm, 700 μm, 800 μm, 900 μm, 1000 μm or any value within the range of any two of the above values. The thickness of the coating liquid film can further be 500 μm to 1000 μm.

[0048] Step S3, immersing the coating liquid film in a proton solvent for curing, and then removing the proton solvent to obtain a flexible functional ceramic-based composite film.

[0049] Specifically, the coating liquid film is immersed in a coagulation tank containing a proton solvent for solidification, which further promotes the phase separation and protonation process of the ceramic and nano-aramid fiber in the coating liquid film, thereby forming a stable solid structure. After solidification, it is washed with water to remove impurities such as the proton solvent, residual organic solvent, and reaction by-products, which can improve the purity and performance of the film. Finally, it is dried to further remove moisture to obtain a flexible functional ceramic-based composite film.

[0050] Among them, the nano-aramid fiber forms a nano-aramid fiber layer on the ceramic surface. The amide groups (-CONH - ) and the hydroxyl groups (-OH) grafted on the surface of the ceramic material form hydrogen bonds, which enhances the interfacial bonding force between the surface nano-aramid fiber layer and the ceramic layer, and can provide sufficient flexibility under the conditions of high ceramic filling amount and low nano-aramid fiber addition amount. At the same time, due to the phase separation properties of nano-aramid fibers, nano-aramid fibers are unevenly distributed in the flexible functional ceramic-based composite film. When the flexible functional ceramic-based composite film is bent, the nano-aramid fiber layer can effectively disperse stress and avoid stress concentration, thereby achieving a comprehensive improvement in the functionality and flexibility of the flexible functional ceramic-based composite film.

[0051] For example, the flexible functional ceramic-based composite film can be a flexible two-dimensional boron nitride-based composite film, which has the characteristics of high thermal conductivity, excellent heat dissipation performance and easy large-scale production, and shows broad application prospects in the fields of high-performance thermal management, flexible packaging, automobile manufacturing, aerospace and other industries.

[0052] It can be understood that the preparation method provided in this application is not only applicable to two-dimensional boron nitride ceramic materials, but can also be used to prepare a variety of flexible functional ceramic-based composite films including zero-dimensional, one-dimensional and two-dimensional, such as flexible LLZO-based composite films.

[0053] In some embodiments, the proton solvent may include at least one of water, alcohol, and acid, which helps to improve the curing efficiency, promote the cross-linking reaction, and improve the structure and performance of the flexible functional ceramic-based composite film. The proton solvent may further be an acid solvent, which helps to form a flexible functional ceramic-based composite film structure with finer internal fibers.

[0054] In some embodiments, the drying temperature may be 30° C. to 80° C. and the drying time may be 8 h to 10 h, which is beneficial for completely drying the flexible functional ceramic-based composite film without being damaged while maintaining its flexibility and functionality.

[0055] Compared with the prior art, the method for preparing the flexible functional ceramic-based composite film provided in the embodiment of the present application has the following beneficial effects: 1. The flexible functional ceramic-based film is prepared by using a blade coating technique from a precursor solution of a mixture of a dimethyl sulfoxide-ceramic solution and a nano-aramid fiber solution, which is conducive to achieving a comprehensive improvement in the ceramic functionality and flexibility of the flexible functional ceramic-based film. This preparation method also simplifies the preparation process, reduces production costs, breaks through the limitations of size and scale, and is conducive to industrial large-scale production.

[0056] 2. After further mixing and grinding the isopropyl alcohol and the ceramic material, the solvent is replaced with dimethyl sulfoxide to prepare a dimethyl sulfoxide-ceramic solution. On the one hand, the hydroxyl group (-OH) on the surface of the ceramic material can be grafted with the amide group (-CONH-) of the nano-aramid fiber layer to form a hydrogen bond, thereby improving the binding force between the two; on the other hand, the mixing effect with the nano-aramid fiber solution can be improved, thereby reducing the risk of poor agglomeration of the nano-aramid fibers after blending.

[0057] 3. Due to the phase separation properties of nano-aramid fibers, the nano-aramid fibers are unevenly distributed in the flexible functional ceramic-based composite film to form a non-homogeneous structure. When the flexible functional ceramic-based composite film is bent, the nano-aramid fibers can effectively disperse stress, avoid stress concentration, and improve the flexibility of the flexible functional ceramic-based composite film.

[0058] 4. This application has wide applicability and can be used to prepare a variety of flexible functional ceramic-based composite films including zero-dimensional, one-dimensional and two-dimensional ones, which significantly expands the application fields and market prospects of functional ceramic materials, provides technical support for the design and development of new high-performance ceramic materials, and promotes the widespread application of functional ceramics in cutting-edge science and technology.

[0059] An embodiment of the present application also provides a flexible functional ceramic-based composite film, which is prepared by the above-mentioned method for preparing a flexible functional ceramic-based composite film, and the flexible functional ceramic-based composite film has a heterogeneous structure.

[0060] Compared with the prior art, the flexible functional ceramic-based composite film provided by the embodiment of the present application can achieve high flexibility of the film without sacrificing the functionality of the ceramic. The heterogeneous structure of the flexible functional ceramic-based composite film is conducive to dispersing stress and improving its flexibility.

[0061] The above-mentioned flexible functional ceramic-based composite film and its preparation method are further described below through specific examples.

[0062] Example 1 Step 1, ball-milling boron nitride (BNNS) ceramic material and isopropanol solvent to obtain a ceramic material solution, wherein the solid content is 15wt%, the rotation speed is set to 350rpm, and the ball-milling time is 48h, and then the ceramic material solution is centrifuged twice at a rotation speed of 10000rpm, and the isopropanol solvent is replaced with dimethyl sulfoxide solvent to obtain a dimethyl sulfoxide-ceramic solution; 3g of polyparaphenylene terephthalamide fiber is dissolved in 100mL of dimethyl sulfoxide, 12mL of water and 4.5g of potassium hydroxide, and heated and stirred for 24h at a heating temperature of 50°C and a stirring speed of 100rpm to obtain a nano-aramid fiber solution; the above-mentioned dimethyl sulfoxide-ceramic solution and the nano-aramid fiber solution are blended in a mass fraction ratio of 85:15, and stirred to form a uniform precursor solution, and the mass ratio of ceramic material to nano-aramid fiber in the precursor solution is 32:1.

[0063] Step 2: Scrape the precursor solution onto the surface of the coating substrate at a linear speed of 30 mm / s and a coating thickness of 1000 μm to obtain a coating liquid film with a thickness of 1000 μm.

[0064] Step 3: Immerse the coating liquid film in a coagulation tank containing an acetic acid proton solvent for solidification. After the color changes from yellow to white, the solidification is completed. Then wash with water to remove impurities and dry at 60° C. for 24 hours to obtain a flexible functional ceramic-based composite film.

[0065] Example 2 The specific process of the preparation process refers to Example 1. The difference from Example 1 is that in step 1, the mass ratio of ceramic material to nano-aramid fiber in the precursor solution is 10:1. The rest of the preparation method is basically the same as Example 1 and will not be described in detail here.

[0066] Example 3 The specific process of the preparation process refers to Example 1, and the difference from Example 1 is that the coating thickness is 500 μm, and the rest of the preparation method is basically the same as Example 1, which will not be described in detail here.

[0067] Comparative Example 1 Step 1: Slowly add water to the deprotonated nano-aramid fiber solution at a ratio of 10:1 (water: nano-aramid fiber solution) to achieve re-protonation. At the same time, during the water addition process, a 500 rpm rotor is used for stirring to avoid a large amount of agglomeration. Then, further homogenization is performed by a cell disruptor to obtain a re-protonated nano-aramid fiber solution.

[0068] Step 2: Mix the reprotonated nano-aramid fiber solution with the boron nitride ball-milled with isopropanol to obtain a precursor solution, and prepare a boron nitride / nano-aramid fiber composite film by vacuum-assisted filtration. The mass ratio of boron nitride to nano-aramid fiber in the precursor solution is 32:1.

[0069] Comparative Example 2 The specific process of the preparation process refers to Comparative Example 1. The difference from Comparative Example 1 is that in step 2, the mass ratio of ceramic material to nano-aramid fiber in the precursor solution is 10:1, and the rest of the preparation method is basically the same as Comparative Example 1, which will not be described in detail here.

[0070] The composite films in the above Examples 1-3 and Comparative Examples 1-2 were subjected to flexibility tests.

[0071] Flexibility test method: In the bending test, a composite film of the same size is placed vertically between two horizontal planes and gradually approaches the two horizontal planes to cause the composite film to bend. When the critical bending radius is reached, the film changes from the original bending state to a state with a sharp angle. The critical bending radius is recorded and analyzed by video, and its value (defined as r b ), and the flexibility of the composite film is defined as f = 1 / r b , the results are shown in Table 1.

[0072] The results show that compared with comparative examples 1-2, the flexible functional ceramic-based composite films in embodiments 1-3 all have good flexibility. This is because the scraping technology is combined with the solidification of the precursor solution in a proton solvent, resulting in phase separation, resulting in a non-homogeneous flexible functional ceramic-based composite film, which is beneficial to disperse stress and improve the flexibility of the flexible functional ceramic-based composite film.

[0073] The composite films in Example 1 and Comparative Example 1 have the same ceramic filling amount and thickness, but the composite film prepared in Comparative Example 1 is a homogeneous structure with poor flexibility. It cannot be bent at this high ceramic filling amount, which shows that the flexible functional ceramic-based composite film of the embodiment of the present application can effectively take into account both ceramic functionality and flexibility. The composite films in Example 2 and Comparative Example 2 also have the same ceramic filling amount and thickness. At the same ceramic filling amount, the flexibility of Example 2 reaches 0.422mm -1 , while the comparative example 2 is only 0.040mm -1 .

[0074] It is to be understood that the above embodiments are merely exemplary embodiments used to illustrate the principles of the present invention, but the present invention is not limited thereto. For those of ordinary skill in the art, various modifications and improvements can be made without departing from the spirit and essence of the present invention, and these modifications and improvements are also considered to be within the scope of protection of the present invention.

Claims

1. A method for preparing a flexible functional ceramic-based composite film, characterized in that: include: mixing a dimethyl sulfoxide solution containing a ceramic material with a nano-aramid fiber solution to obtain a precursor solution; Scrape the precursor solution onto the surface of the carrier to form a coating liquid film; as well as After the coating liquid film is immersed in a proton solvent for solidification, the proton solvent is removed to obtain the flexible functional ceramic-based composite film.

2. The method for preparing a flexible functional ceramic-based composite film according to claim 1, characterized in that: The preparation of the dimethyl sulfoxide solution containing ceramic material comprises the following steps: mixing the ceramic material with the isopropyl alcohol solvent and grinding the mixture to obtain a ceramic material solution; and The isopropyl alcohol solvent in the ceramic material solution is replaced with a dimethyl sulfoxide solvent to obtain the dimethyl sulfoxide solution containing the ceramic material.

3. The method for preparing a flexible functional ceramic-based composite film according to claim 2, characterized in that: In the step of grinding the ceramic material with the isopropanol solvent, the grinding speed is 300 rpm to 600 rpm, the grinding time is 24 h to 48 h, and the grinding includes at least one of ball milling and sand milling; and / or In the step of replacing the isopropanol solvent in the ceramic material solution with a dimethyl sulfoxide solvent, a centrifugal replacement method is adopted, and the conditions of the centrifugal replacement include: a rotation speed of 10000rpm~11000rpm, a time of 20min~25min, and a centrifugal number of 1~2 times.

4. The method for preparing a flexible functional ceramic-based composite film according to claim 1, characterized in that: The ceramic material includes at least one of a zero-dimensional ceramic material, a one-dimensional ceramic material and a two-dimensional ceramic material.

5. The method for preparing a flexible functional ceramic-based composite film according to claim 1, characterized in that: The nano-aramid fiber solution is prepared by alkaline lysis method, comprising the following steps: The aramid precursor is dissolved in a mixed solution of dimethyl sulfoxide and potassium hydroxide, and the mixture is heated and stirred to obtain the nano-aramid fiber solution.

6. The method for preparing a flexible functional ceramic-based composite film according to claim 1, characterized in that: The nano-aramid fiber in the nano-aramid fiber solution includes at least one of para-aramid, heterocyclic aramid and meta-aramid.

7. The method for preparing a flexible functional ceramic-based composite film according to claim 1, characterized in that: In the precursor solution, the mass ratio of the ceramic material to the nano-aramid fiber is (1-32):

1.

8. The method for preparing a flexible functional ceramic-based composite film according to claim 1, characterized in that: The linear speed of the scraping is 20 mm / s to 90 mm / s; and / or The coating liquid film has a thickness of 250 μm to 1000 μm.

9. The method for preparing a flexible functional ceramic-based composite film according to claim 1, characterized in that: The protic solvent includes at least one of water, alcohol and acid.

10. A flexible functional ceramic-based composite film, characterized in that: The flexible functional ceramic-based composite film is prepared by the preparation method of any one of claims 1 to 9.